Investigating the Effects of Exposure to Waterpipe Smoke on Pregnancy Outcomes Using an Animal Model - Khabour, Omar F. (Nicotine Tob Res, 2016)
INTRODUCTION: In recent years, waterpipe tobacco smoking has been increasing in popularity all over the world. In this study, we explored effects of waterpipe smoking on pregnancy outcomes in rats. METHODS: Animals were exposed to waterpipe tobacco smoking using a whole body exposure system 2 hours per day during pregnancy. A control group was exposed to fresh air only. RESULTS: The results showed significant association between exposure to waterpipe smoke during pregnancy and low birth weight ( P < .01) and neonatal death ( P < .01). In addition, the rate of growth of offspring of the waterpipe group was significantly lower than that of control group as measured by body weight gain during the first 3 months of life ( P < .001). No effect was found for waterpipe smoking on mean number of progeny and male to female ratio among offspring. CONCLUSION: Waterpipe smoking is associated with adverse effects on pregnancy outcomes. IMPLICATIONS: In this study, we investigated for the first time the effect of waterpipe smoking on pregnancy outcomes using animal model. The results clearly showed that waterpipe smoking is associated with adverse effects on pregnancy outcomes that include low birth weigh, neonatal survival, and growth retardation.